A Preliminary Study on Kinematics Model of A Bipedal Robot - David Kurniawan; Prianggada I Tanaya; Tony Prahasto (Jurnal Elektro, 2015)
This paper presents a simulation of motion of a bipedal robot and a comparison between the result of simulation and the actual robot. The hip and the knee are modeled as one degree of freedom (DOF) hinge respectively. The traction or gait is modeled as nonlinear joint alternating between one DOF pin joint and losing contact modes during the motion of the robot. The motion is modeled as a plane motion and the equation of motion is developed using the Lagrangian method. Besides torque, the jerk and impacts during the motion are observed and analyzed in the simulation. A spread sheet analysis is also performed to confirm and verify the result of simulation. In the actual robot, a PID control system is used. Various values of PID gains are set for the experiments, and the resulting behavior of the robot is observed.